The Existence of the Davos Factory in the Midst of the Dutch East Indies Government's Economic Depression in Purbalingga 1931-1939 - Anita Harsika Damayanti; Ufi Saraswati (Universitas Islam Negeri Sumatera Utara, 2026)
The global economic depression of the 1930s, which also rocked the Dutch East Indies, had a significant impact on the colonial economic structure, particularly on the plantation sector and the sugar industry, the mainstay of the Javanese economy. In the Banyumas Residency area, this situation was marked by declining production and rising unemployment. Amidst these unstable economic conditions, the Davos Factory in Purbalingga was able to survive and maintain its business continuity. This study aims to examine the background to the establishment of the Davos Factory in the context of the economic depression, analyze its existence during the period 1931–1939, and identify factors that supported its resilience. This study uses a historical method that includes heuristics, source criticism, interpretation, and historiography. Research sources were obtained from colonial archives, contemporary newspapers, company documents, and interviews with historical witnesses. The results of the study indicate that the sustainability of the Davos Factory was supported by adaptation strategies through product diversification, consistency in maintaining quality and taste identity, adjusting production scale to market conditions, and strengthening internal social networks through a hereditary labor recruitment system. The Davos factory also served as an economic pillar for the surrounding community. These findings demonstrate that small-scale local industries had sufficient capacity to survive the pressures of the colonial economy.